Produção científica sobre educação médica no Brasil: estudo a partir das publicações da Revista Brasileira de Educação Médica - Hamamoto Filho, Pedro Tadao [UNESP]; Santos Filho, Carlos Alberto [UNESP]; Abbade, Joelcio Francisco [UNESP]; Peraçoli, José Carlos [UNESP] (Associação Brasileira de Educação Médica, 2013)
Research in medical education is the critical and systematic study of teaching and learning in medicine. It's a developing field with an increasing number of researchers and publications. In Brazil, the Brazilian Journal of Medical Education (RBEM) is the main journal in the area. The present study describes Brazilian scientific production in medical education by analyzing papers published by the RBEM from 2006 to 2010. In this period, the number of articles increased by 117.6%, averaging 60.4 articles per year. There was also an increase in the proportion of new research studies. The Southeast region and public institutions account for the greatest share of the articles. The most frequent keywords were medical education, medical students and curriculum. The growth of the RBEM reflects the development of research in medical education in Brazil and is in keeping with the logic of national scientific production.

A pesquisa em educação médica é o estudo crítico e sistemático do ensino e aprendizagem em Medicina. É um campo em crescimento, em número tanto de pesquisadores envolvidos, como de produções geradas. No Brasil, a Revista Brasileira de Educação Médica (RBEM) é o principal meio de divulgação científica da pesquisa da área. Este estudo visa caracterizar a pesquisa em educação médica brasileira a partir das publicações da RBEM no período de 2006 a 2010. Neste período, houve um crescimento de 117,6%, com média de 60,4 artigos por ano, com crescente participação proporcional de pesquisas inéditas. A Região Sudeste e instituições públicas têm a maior participação nos artigos. Os descritores mais utilizados foram educação médica, estudantes de Medicina e currículo. O crescimento da RBEM espelha o desenvolvimento da pesquisa em educação médica brasileira, seguindo a lógica da produção científica nacional.
Scientific production on pedical education in Brazil: a Study based on the Brazilian Journal of Medical Education
Keywords: Educação Médica; Pesquisa em Educação Médica; Produção Científica; Medical Education; Research in Medical Education; Scientific Production